Accelerating the United Nation's 2030 Global Agenda: Why Prioritization of the Gender Goal is Essential - Paula Hepp; Claire Somerville; Bettina Borisch (Global Policy, 2019)
In September 2015, Member States of the United Nations (UN) committed to work towards a transformative policy agenda consisting of 17 ambitious Sustainable Development Goals (SDGs) to be achieved by 2030. However, implementation progress has been slow and at the current rate the SDG agenda will fall far short on delivery of its 169 targets. In order to accelerate progress at global, national and local levels it is necessary to prioritize goals and targets. One standalone SDG that is also cross-cutting and universal is Goal 5: Gender equality and empowerment of all women and girls. In this article we assemble evidence to make the case that decisively (and politically) placing the gender equality goal (SDG5 and its 9 targets) together with 54 gender indicators across all goals as the priority focus of the 2030 agenda is the most impactful way to ensure measurable achievements are made across the agenda to deliver on all 5 pillars of the global commitment: namely People, Planet, Peace, Prosperity and Partnerships.
Keywords: 320